Stereotactic body radiation therapy or conventional fractionated radiotherapy combined with immune checkpoint inhibitors? From biological perspectives - Liu, Yanmei; Ye, Ganghui; Chen, Weijun; Ding, Yan; Ying, Shenpeng; Wu, Shixiu (Frontiers in Immunology, 2025)
We focused on a paper titled “Radiation with immunotherapy may be a double-edged sword—how can we learn from recent negative clinical trials?”, which was published in JAMA Oncology recently. Herein, we initially provided three complementary viewpoints from biological perspectives involved in the dynamic alterations of the tumor microenvironment, which may contribute to a more comprehensive understanding of the superiority of stereotactic body radiation therapy (SBRT).